ZEMSTVO QUESTION IN PUBLIC-STATE INTERACTION IN THE CAUCASUS IN THE LATE 19TH – EARLY 20TH CENTURY - PRASOLOV, D.N. (Kavkazologiya, 2020)
On the example of public-state interaction on the problem of the establishment of zemstvo self-government in the Caucasus the formation and functioning of the public sphere in the South of Russia, included in the all-Russian space of public opinion, is considered. At the end of the 19th century the regional zemstvo movement manifested itself in the form of public discussions of the models of expected transformations. To the north and to the south of the Caucasus range this process took place rather separately. Thus the all-Russian zemstvo tradition served as a model, but the Caucasian figures repeatedly declared the necessity of taking into account the specificity and local traditions of public self-organization. With the restoration of the Caucasian Viceroyalty in 1905 the Zemstvo question began to be discussed in an organized dialogue with the authorities from above, reaching the level of the Council of Ministers and the State Duma. The study identifies the main stages, directions and forms of representation of the ideas of the introduction of zemstvo institutions in the Caucasus region. It reveals a significant influence of regional journalism on the formulation, discussion and public control of zemstvo initiatives, which were largely made possible with the assistance of the Caucasian viceroyalty, which sought greater autonomy from the capital authorities. However, the regional public sought more than the imperial administration in the Caucasus was capable of organizing in the socio-political conditions of the early 20th century. Without achieving the establishment of zemstvos, the participants of the zemstvo movement in the Caucasus carried out considerable zemstvo work: from the analysis of the socio-economic situation based on considerable statistical and research work to project planning, contributing by their activity to the formation of the main features of the public sphere as an open sphere of rational-critical debates around public problems. However, forming the primary parameters of civil society and modern public consciousness, overcoming the corporate framework and elaborating the bases of ethno-political ideologies, the public of different territories of the Caucasian Region were more and more settling in the regional understandings of their zemstvo needs, which in all contradiction of creative and destructive power showed itself in the public policy under the influence of the Revolution of 1917.